2021
DOI: 10.1038/s41561-021-00711-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired viral infection and reduced mortality of diatoms in iron-limited oceanic regions

Abstract: Diatoms contribute up to 40% of marine primary production 1 and have silicified cell walls that ballast substantial vertical flux of particulate organic matter out of the surface into the deep ocean 2 . In high-nutrient, low-chlorophyll regions of the open ocean and along some coastal upwelling margins, iron (Fe) availability limits diatom production [3][4][5] and may contribute to the decoupling of primary productivity and export efficiency in these waters [6][7][8] . Fe-limited waters are biogeochemically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…For example, an investigation suggested that aggregate formation and vertical carbon fluxes were enhanced by the Coccolithovirus infections of coccolithophore, Emiliania huxleyi , blooms in the North Atlantic [ 86 ]. These indicate that viral infection can “shuttle” surface organic particles into deep waters, and may promote the efficiency of BP in the ocean [ 87 ]. In this study, for the first time, we revealed that environmental changes caused by vertical transplantation decreased the VMM, but significantly increased lytic and lysogenic VP by increasing BS and triggering the switch from the lysogenic to lytic strategy to release additional viral particles into the surrounding water (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an investigation suggested that aggregate formation and vertical carbon fluxes were enhanced by the Coccolithovirus infections of coccolithophore, Emiliania huxleyi , blooms in the North Atlantic [ 86 ]. These indicate that viral infection can “shuttle” surface organic particles into deep waters, and may promote the efficiency of BP in the ocean [ 87 ]. In this study, for the first time, we revealed that environmental changes caused by vertical transplantation decreased the VMM, but significantly increased lytic and lysogenic VP by increasing BS and triggering the switch from the lysogenic to lytic strategy to release additional viral particles into the surrounding water (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This so-called viral shuttle was shown in laboratory experiments for diatoms [ 51 ]. For diatoms in iron-limited waters (such as the Southern Ocean), another shuttle system (the so-called viral shuttle) has also recently been suggested, based on a combination of increased silicate in diatom shells and delayed virus-induced mortality [ 116 , 117 ]. Both the viral shunt and viral shuttle, however, would still decrease the trophic transfer efficiency compared to grazing-dominated systems.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that none of the dominant diatom genera responded to Fe-limitation by thickening frustules complements previous field studies in both the Equatorial Pacific [ 6 ] and CUZ [ 28 ], lying in stark contrast to studies that suggest diatom frustule thickening is a common response to Fe-limitation [ 2 ]. Thus, evaluation of drivers of carbon export and opal burial in Fe-limited regimes must also consider mechanisms that do not depend on increased silica ballasting, such as increased aggregation [ 77 ], reduced grazing and associated respiratory losses [ 5 ], and viral infection [ 78 ].…”
Section: Discussionmentioning
confidence: 99%